The Effectiveness of Bedside Handover Training Based on Patient-Family Centered Care at Nurses on Patient Safety at the Tgk Regional General Hospital Chik Di Tiro Sigli - Ismuntania; Dewiola, Sara; Idawati; Kartika; Mufida, Nurlela (International Journal on ObGyn and Health Sciences, 2023)
The patient- and family-centered professional care model is called Patient-Family Centered Care (PFCC). PFCC is the latest service method that is being developed and is considered to have a good impact on patient safety. PFCC is a new challenge for nurses because they must involve patients and families when providing care. Bedside handover is a form of service that is offered in the form of a care process between shifts. The purpose of this study was to determine the effectiveness of PFCC-based bedside handover training for nurses on patient safety at RSUD. Tgk Chik Di Tiro Sigli. The stages start from the preparation stage, namely the start of cases and literature, the implementation stage by collecting data and the analysis stage by analyzing the data findings. The design of this study used a quasi-experimental approach with a one group pretest-posttest design approach. Patient safety will be measured before and before being given PFCC-based bedside handover training. The data collection method was carried out by measuring the quality of patient safety using a questionnaire before and before presenting the training. Data analysis used Paired Test with a significance level of 95%. The results of the study: the probability value (0.000) means that the Ho data is rejected. The bed handover training based on patient-family-centered care is very effective in improving the implementation of good patient safety at the Tgk Chik Di Tiro Sigli Regional General Hospitalaa